2021
DOI: 10.1001/jamanetworkopen.2021.6322
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Sentinel Lymph Node Biopsy and Radiotherapy in Older Women With Early-Stage, Estrogen Receptor–Positive Breast Cancer

Abstract: IMPORTANCE Overtreatment of early-stage breast cancer with favorable tumor biology in older patients may be harmful without affecting recurrence and survival. Guidelines that recommend deimplementation of sentinel lymph node biopsy (SLNB) (Choosing Wisely) and radiotherapy (RT) (National Comprehensive Cancer Network) have been published. OBJECTIVE To describe the use rates and association with disease recurrence of SLNB and RT in older women with breast cancer. DESIGN, SETTING, AND PARTICIPANTS This cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…23 A large cohort study of more than 3000 older women, aged 70 years and older, at a single health-care system revealed that performing SLNB in this subgroup provided no outcome advantages with respect to locoregional recurrence or breast cancer-specific survival. 10 Some recommendations, such as those from EUSOMA–SIOG, state that SLNB should only be omitted for frail patients with low-volume, luminal A-like tumours. 24 However, emerging evidence posits that SLNB omission can be extended to many more patients: even omitting SLNB in the setting of higher-grade or higher-stage disease did not affect disease-free or locoregional recurrence-free survival.…”
Section: Clinical Trends In De-implementation In Low-risk Breast Cancer In Older Womenmentioning
confidence: 99%
See 4 more Smart Citations
“…23 A large cohort study of more than 3000 older women, aged 70 years and older, at a single health-care system revealed that performing SLNB in this subgroup provided no outcome advantages with respect to locoregional recurrence or breast cancer-specific survival. 10 Some recommendations, such as those from EUSOMA–SIOG, state that SLNB should only be omitted for frail patients with low-volume, luminal A-like tumours. 24 However, emerging evidence posits that SLNB omission can be extended to many more patients: even omitting SLNB in the setting of higher-grade or higher-stage disease did not affect disease-free or locoregional recurrence-free survival.…”
Section: Clinical Trends In De-implementation In Low-risk Breast Cancer In Older Womenmentioning
confidence: 99%
“…Even in the absence of a randomised trial, omission of SLNB from routine care is possible as: (1) there is limited diagnostic utility from the procedure; (2) with a clinically node-negative axilla, only some of these patients will actually have a pathologically positive node; and (3) in older women with early-stage disease, omitting SLNB will have a small absolute increase in recurrences without a detriment to their disease-free survival. 10 …”
Section: Clinical Trends In De-implementation In Low-risk Breast Cancer In Older Womenmentioning
confidence: 99%
See 3 more Smart Citations